Invisible victims of induced abortions in the kingdom of Yugoslavia in the 1930s - Jorgić-Stepanović Kristina (Temida, 2019)
The author gives a detailed analysis of the 1929 Criminal Code paragraphs that pertain to abortion. Analyzing the social indications, the paper also explains the methodological inability to determine the precise number of abortions performed during the 1930s. However, the subject of this paper is not solely an exploration of legal regulations on abortions, but rather the identification of the treatment of women in the Yugoslav Kingdom’s Criminal law from this point of view. Considering that the problem of induced abortions was approached from the existing conservative- patriarchal socio- political position, the press was often the key source for analyzing and documenting this problem. Precisely because of this fact, the paper presents an affair that revolved around the work of gynaecologist Pance Stojanovic in mid-summer 1936. This case showed the deep corruption of the Yugoslav society, but also the involvement of various representatives of power in this affair. It turned out that the patients were women from different backgrounds, but that girls and women from affluent families were far more numerous. Faced with the increasing number of fatalities following induced abortions, doctors at the 17th Congress of the Serbian Medical Association called for changes to the articles of the Yugoslav Criminal Code relating to abortion.